أخلاقیات الذکاء الاصطناعى والروبوت دراسة تحلیلیة - د.خدیجة محمد درار (المجلة الدولية لعلوم المكتبات والمعلومات, 2019)
This study aimed to identify the concept of artificial intelligence, bystudy the ethical aspects and issues associated with it, and the fears that mayarise from the self-awareness of robots to come up with local policies proposedfor the ethics of artificial intelligence by studying and analyzing the reality ofartificial intelligence policies in the study community, which represent 5 globalpolicies: Information Technology Industry Council Policy ITI, IEEE Global Policy,Laurel Rick and Don Howard Policy in HRI Research, European RoboticsResearch Organization Policy EUORN, the policy of Federal Ministry ofTransport and Infrastructure in Germany.This study concluded with a number of results, the most prominent is :The Arab world is devoid of the ethical policies of artificial intelligence , None ofthe policies in question met the criteria of the Equivalency Standard, which statesthat robots provide all services and functions required for all users of differentcultures, ages, nationalities and economic levels, The policy of the FederalMinistry of Transport and the infrastructure of the Government of Germany hasreceived the highest standards of ethics Artificial intelligence and robot as 48.7%.Where robots are equal to humans in the Actions that will taken when robots failto work, there is a clear need for further development and improvement in thestandards of artificial intelligence robot.  In light of the results, the researcher made a number ofrecommendations: The Arab universities and research centers should adopt theethics of robotics and robotics systems and work on scientific research to developand support policies in this field. Planning a workshop aimed at educating theindividual and society about the importance of looking at artificial intelligence androbots in terms of ethics, cooperation between official and governmental bodies  and other competent bodies in the field of artificial intelligence around the worldto benefit from the news. Cooperation between the official and governmentagencies and other competent authorities in the field of artificial intelligencearound the world to benefit from the expertise, experience and laws available andreached in this field, Establish an international Arab committee on artificialintelligence to develop a strategic plan for the ethical policies of artificial